Crystal growth behavior and phase stability of rare earth oxides (4 mol.% GdO1.5-4 mol.% SmO1.5) doped zirconia nanopowders - R. Mahendran; S. Manivannan; S. Senthil Kumaran; A. Vallimanalan; M. Murali; S. Gokul Raj; S. P. Kumaresh Babu (Journal of Materials Research and Technology, 2019)
Nanocrystalline powders of 4 mol.% GdO1.5-4 mol.% SmO1.5 doped ZrO2 (4Gd4SmSZ) has been synthesized by co-precipitation process. Their phase transformation and crystalline growth behavior was investigated by Thermo gravimetric-Differential Thermal Analysis (TG-DTA), X-ray Diffraction (XRD), Raman spectroscopy and High-Resolution Transmission Electron Microscopy (HR-TEM) after calcinations at different temperatures. The XRD, Raman spectra and HRTEM results confirm the nature of tetragonal zirconia (t-ZrO2). The prepared 4Gd4SmSZ powders, remains in the single metastable tetragonal phase over the whole calcination temperature ranging from 873 K to 1273 K for 2 h. The crystallite size varies from 11.98 nm to 18.90 nm with increase of temperature from 873 K to 1273 K. The activation energy of the prepared powders at low temperature is considerably lesser than that at a higher temperature. The annealed 4Gd4SmSZ powders had shown excellent phase stability at 1573 K for 100 h. Keywords: Zirconia, Coprecipitation, Rare earth oxide, Phase transformation, Tetragonal, Activation energy